ANALYSIS OF SOCIAL PROBLEMS CAUSING THE GROWTH OF INTOLERANCE IN UZBEKISTAN (Scientific journal of the Fergana State University, 2026)
An analysis of social problems causing the manifestation of tolerance to others and the intensification of intolerance to others in Uzbekistan is presented. At the same time, the changes in tolerance in our society and the social factors influencing it are studied.